Digital Marketing Development Strategy in Non-Profit Organizations (Study at SOS Children’s Villages Indonesia) - Sumanda Purba Tondang; Yohana Yohana; Meilani Meilani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Digital marketing strategies have become the main focus in increasing a company's sales, especially after the pandemic that hit, causing all strategies to be forced to maximize digital technology and online communication channels, and non-profit organizations are no exception. This research identifies various digital marketing strategy developments carried out by SOS Children's Villages Indonesia, especially to get long-term support from the public. The research was conducted using a qualitative approach with two methods namely interviews and observation. The resource persons are employees who have worked at SOS Children's Villages for more than two years and also have positions at the managerial level and are experts in their fields. The results obtained from this study found that communication patterns that focus on the impact of social programs that have been carried out by the organization so far will be one of the factors to increase the credibility of SOS Children's Villages thereby causing an increase in public support. Recommendations that can be given to organizational management are to be consistent in new innovations in the use of technology, as well as merging offline activities in parallel with communication messages carried out through online channel.